THE GIVEN PROBABILITIES ARE B(M1) FOR M1-TRANSITIONS FROM STATES TO STATES AND OF THE BASEBAND OF THE 156Gd NUCLEUS (Web of Technology: Multidimensional Research Journal, 2024)
For the 156Gd nucleus, theoretical calculations were carried out within the framework of the phenomenological model, taking into account the Coriolis mixing of the states of low-lying positive-parity rotational bands. The Coriolis interaction makes it possible to explain the nonadiabaticity effects observed in the properties of excited states. Reduced probabilities of M1-transitions from vibrational states are calculated. The agreement between the theoretical results and experimental data is generally satisfactory.